Estimation of heritability and genetic parameters for carcass traits and primal cut production traits in Hanwoo - Jae Don Oh; Gwang Hyeon Lee; Hong Sik Kong (The Korean Society of Animal Reproduction and Biotechnology, 2024)
Background: The Hanwoo industry must develop technologies that can increase the production of preferred cuts to match changing consumer trends. In this study, we aimed to estimate the genetic parameters for carcass traits (carcass weight, eye muscle area, back fat thickness, and intramuscular fat) and primal cut traits (tenderloin, loin, strip loin, neck, clod, top round, bottom round, brisket, shank, and rib) in a Hanwoo population to obtain basic data for improving primal cut productivity. Methods: Data from 1,905 Hanwoo steers, including carcass traits and primal cut weights, were collected. Genetic parameters were estimated using REMLF90 in a multi-trait analysis. Results: High heritability was found for carcass weight (0.52) and strip loin yield (0.63). Genetic correlations between carcass weight and primal cut weights ranged from 0.52 to 0.93. Conclusions: This study demonstrates the significant potential for genetic improvement in Hanwoo cattle through selective breeding, particularly for traits with high heritability and genetic correlations. These findings provide crucial insights into optimizing breeding programs to improve Hanwoo cattle production efficiency.